Postal Market Solutions in The Context of Digital Economy and Megatrends: Example of The Polish Market - Anna DRAB-KUROWSKA; Michał KUŚCIŃSKI (Communications of International Proceedings, 2021)
The article discusses changes taking place in the current economy, which is described as the digital economy. The article also highlights megatrends which have a significant impact on the logistics sector in general, and the postal market in particular. The aim of the article is to analyze the theory of the digital economy and megatrends which increasingly often affect all sectors of the economy, including logistics and postal services. An attempt has been also made to answer a research question about future business models in the postal sector. The following research methods were used to achieve the assumed goal. A critical analysis of the domestic and foreign-language literature on the subject of the functioning of the postal services market was carried out and based on own observations of the Polish postal services and e-commerce market. The first part of the article defines the concept of the digital economy. This has enabled to develop a multi-faceted definition of the term. The article describes specific characteristics of the digital economy while emphasizing megatrends on the market. The discussion also covers the e-commerce market, which has seen on a strong growing path in the last decade. Handling of this market is a huge challenge for postal operators who need to cope with a tremendous increase in demand for CEP services (courier, express and parcel mail). On the other hand, digitalization of the economy and society lead to a significant drop in the demand for traditional postal services.  The authors have presented solutions planned in this respect. These solutions are either e-services or hybrid services.
Keywords: postal market; e-commers; logistics solutions